Healthcare waste management practices' identification and evaluation to rank hospitals. (2018) - Chauhan, Ankur; Singh, Amol; Jharkharia, Sanjay
In the present study, various criteria (practices) have been identified from the literature of healthcare waste management. The analytic hierarchy process (AHP) has been applied to compute the weights of these criteria. The weight of a criterion shows its significance for healthcare waste management. Furthermore, the weights of criteria have been used as an input to Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), for ranking six alternatives (hospitals) to demonstrate the assessment methodology in real time. The literary contribution of this work is the identification of HCWM practices, which can be very useful in the assessment of the hospital's waste management planning, shown by the case study.